The activity and expression of adenylosuccinate lyase were reduced during modern human evolution, affecting brain and behavior - Xiang-Chun Ju; Shin-Yu Lee; Richard Ågren; Luiz Carlos Machado; Jiawei Xing; Chika Azama; Michael C. Roy; Toshihiro Endo; Wieland Huttner; Adam Siepel; Izumi Fukunaga; Hugo Zeberg; et al. (Proceedings of the National Academy of Sciences, 2025)
Adenylosuccinate lyase (ADSL), an enzyme that is crucial for purine biosynthesis, carries an amino acid substitution that is present in almost all humans today but absent in Neandertals and Denisovans. This substitution reduces the stability of the enzyme, but what functional consequences it has are unknown. Here, we show that when introduced into mice, this substitution causes substrates of the enzyme to accumulate in amounts that correlate negatively with ADSL expression levels. In the brain, where the expression of the enzyme is low, the substitution results in particularly high substrate levels. When the behavior of the mice is analyzed, female mice expressing the modern human-like version of ADSL access water more efficiently for drinking than their wild-type littermates. In addition to the amino acid substitution, a haplotype in the ADSL gene occurs at a carrier frequency of >97% in present-day humans and exhibits evidence of positive selection. It is associated with less ADSL expression as well as with increased concentrations of succinyladenosine, one of the substrates of the enzyme, in cerebrospinal fluid. Thus, two genetic changes have reduced ADSL activity in human tissues since modern and archaic humans separated, affecting purine biosynthesis, particularly in the brain.